DEVELOPMENT OF THE PERSONAL SELF-DETERMINATION OF SECONDARY SCHOOL STUDENTS IN THE CONTEXT OF THE HUMANITARIAN PARADIGM OF EDUCATION - Alijev, Roman; Chehlova, Zoja; Keviša, Ingrīda (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The research problem is the development of the personal self-determination of secondary school students in the process of learning based on the humanitarization of education. The research has been underpinned by the humanitarian paradigm of education, which is the result of the development of pedagogical methodology. In the 21st century, pedagogy is viewed as a social-humanitarian science with the predominance of the humanitarian component. We regard humanitarization as a contemporary technology of the educational process. The aims of the study are to analyse the characteristics of the personal self-determination of adolescents, identify the structure of the personal self-determination of secondary school students and determine conditions for the development of the personal self-determination of secondary school students in the process of learning. The research methods include observation, survey, conversation, an establishing experiment, mathematical statistics. The research results:1. there was determined the structure of personal self-determination of secondary school students as the system of inter-connected components;2. it was established that the humanitarization of the educational process is the key precondition for the development of the personal self-determination of secondary school students both regarding the logic of the subject and the logic of the process of learning (changing the style of relationships), as well as the logic of education (understanding culture as the world of human attitudes and meanings);3. the key values of secondary school students were identified, which were mainly pragmatic values.